New Design of the Electrophoretic Part of CLARITY Technology for Confocal Light Microscopy of Rat and Human Brains - Zach, Petr; Mrzílková, Jana; Pala, Jan; Uttl, Libor; Kútna, Viera; Musil, Vladimír; Sommerová, Blanka; Tůma, Petr (Brain sciences, 2019)
BACKGROUND: CLARITY is a method of rendering postmortem brain tissue transparent using acrylamide-based hydrogels so that this tissue could be further used for immunohistochemistry, molecular biology, or gross anatomical studies. Published papers using the CLARITY method have included studies on human brains suffering from Alzheimer's disease using mouse spinal cords as animal models for multiple sclerosis. METHODS: We modified the original design of the Chung CLARITY system by altering the electrophoretic flow-through cell, the shape of the platinum electrophoresis electrodes and their positions, as well as the cooling and recirculation system, so that it provided a greater effect and can be used in any laboratory. RESULTS: The adapted CLARITY system is assembled from basic laboratory components, in contrast to the original design. The modified CLARITY system was tested both on rat brain stained with a rabbit polyclonal anti-Iba-1 for microglial cells and on human nucleus accumbens stained with parvalbumin and tyrosine hydroxylase for visualization of specific neurons by confocal laser scanning microscopy. CONCLUSIONS: Our design has the advantage of simplicity, functional robustness, and minimal requirement for specialized additional items for the construction of the CLARITY apparatus.